i-Capacitor Voltage Control for PV Z-source System with Enhanced Shoot-through - Noor Mazliza Badrul Sham; Shamsul Aizam Zulkifli; Ronald Jackson (Institute of Advanced Engineering and Science, 2018)
This paper explains an improved capacitor voltage control (i-CVC) by combining with maximum power point tracking (MPPT) algorithm as a control strategy for a single-phase Z-source inverter (ZSI) using photovoltaic (PV) source. The existing CVC based-MPPT control algorithm has a net shoot-through interval which should be inserted in the switching waveforms of the inverter to produce maximum power at the Z-network of the PV. However, this net shoot-through period is formed by an additional shoot-through period which has drawbacks as it boosts the capacitor voltage to a greater extent beyond the allowable voltage boundary of the capacitor. İn other words, the PV will boost the voltage more than the desired level as per required by reference capacitor voltage of the Z-network. Due to this problem, an improved capacitor voltage control (i-CVC) with general Perturb and Observe (P&O) based on ΔT0’ configuration of the changes shoot-through duty cycle to maintain the DC-link of the ZSI is introduced and been tested in simulation case with a resistive load. At the end, this modification able to assist the MPPT output power by increasing the overall system effectiveness of power generation by the PV.